Dimethyloxalylglycine (DMOG)-induced hypoxia promotes migratory and invasive properties of HCT116 colon cancer cell line - Ahmad, Nor Ezleen Qistina; Mohd Yusoff, Amirah Alhusna; Md Hashim, Nur Fariesha; Abdullah, Nurul Akmaryanti; Muhamad Zakuan, Noraina (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hypoxia, a condition characterised by low oxygen levels, leads to increased production of a protein called hypoxia-inducible factor-1 alpha (HIF-1α) in cancer cells. This protein is involved in driving processes such as vascularization, cytoskeletal reorganisation, and epithelial-to-mesenchymal transformation (EMT), which contribute to metastasis. Previous studies used hypoxic workstations, chambers, and incubators to evaluate the effects of hypoxia on colon cancer cell lines. In a cell culture model, hypoxic conditions can also be induced using dimethyloxalylglycine (DMOG) as the hypoxia-mimicking agent. This study aims to investigate the effects of DMOG-induced hypoxia on colon cancer metastasis, focusing on cell migration and invasion. HCT116 cells were subjected to hypoxic conditions by treating them with DMOG, and the expression of HIF-1α proteins was measured at various time points, followed by wound healing and invasion assays. It was found that HIF-1α protein expression increases after 6 h of DMOG induction and persists for 24 h. At 6 and 24 h, a significantly higher percentage of hypoxic cells migrated compared to normoxic cells. The invasion assay demonstrated that hypoxic cells were more invasive than normoxic cells within 24 h. Thus, the increase in migration and invasion of cells is comparable to the increase in HIF-1α expression at 6 and 24 h. These findings suggest that DMOG induces HIF-1α expression in colon cancer cells, leading to enhanced cell migration and invasiveness. The established model can be further utilised in gene knockdown or drug treatment studies to evaluate the effects of hypoxia on cancer cells.